(untitled) (Communications in Computational Chemistry, 2017)
The reference [J. Org. Chem. 2015, 80, 10817.10828] has reported that the Quinone Methides (QMs) that are of significant medicinal benefits in biological field can be generated via photo-deamination reaction. In this study, the density functional theory (DFT) and time-dependent DFT (TDDFT) methods have been carried out to investigate the reactive mechanisms of free amines compounds 1 and 3. The excited state hydrogen bonding strengthening mechanism has been demonstrated by analyses of frontier molecular orbitals (MOs). Potential energy surfaces (PESs) calculations have been performed for illustrating excited state intramolecular proton transfer (ESIPT) and photo-deamination reactions of forms 1 and 3. The reactive sites of QM1 and QM3 molecules can be accurately predicted via analyses of ESP.